FEATURES OF DIASTOLIC DYSFUNCTION OF THE RIGHT VENTRICLE IN PATIENTS WITH HYPERTENSION - Yarmukhamedova S. Kh.; Vafoeva N. A.; Haydarova Z. E.; Amirova Sh. A. (Academia Science Repository, 2023)
Currently, hypertonic disease is one of the most pressing problems of clinical medicine. This is due to the fact that arterial hypertension leads to disability and mortalityand is also characterized by a wide prevalence. Early diagnosis of diastolic dysfunction of the hearts in hypertensive patients is of great practical interest, which makes it possible to take timely preventive measures and treatment.